Roll-to-roll slot die production of 300 mm large area silver nanowire mesh films for flexible transparent electrodes - Wang, Byung-Yong; Lee, Eung-Seok; Lim, Dae-Soon; Kang, Hyun Wook; Oh, Young-Jei (ROYAL SOC CHEMISTRY, 2017)
To develop flexible transparent electrodes, an ink fabricated with silver nanowires (AgNWs) was coated on a polyethylene terephthalate substrate using a roll-to-roll slot die machine. The AgNW used in the manufacturing of the transparent electrode is a highly transparent conductive material that is very close to commercialization due to its low sheet resistance, low heat treatment temperature, and high transmittance. An AgNW ink was optimized for the slot die process, which was prepared using the optimized formulation with AgNWs, solvent, and dispersant. As a result, high-quality transparent conductive films were successfully manufactured with 32-94 Omega sq(-1) of sheet resistance, 1.3-3.2 of haze and 86.2-92% transmittance with a width of 300 mm. To verify the possibilities in optoelectronic applications, organic solar cells were fabricated with the AgNW mesh transparent electrode and showed a good performance of 7.65% efficiency, which was better than the result obtained using an indium tin oxide-based electrode.
Keywords: ORGANIC SOLAR-CELL; POLYMER